Parenting Patterns in Educating Children to Memorize the Qur’an (Case Study in Percut Sei Tuan) - Assannur, Assannur; Nahar, Syamsu; Salminawati, Salminawati (Graduate Program Magister Manajemen Pendidikan, 2023)
This study aims to determine how parenting styles are applied in teaching children to memorize the Qur’an. This research is qualitative research with descriptive methods by interviewing parents of students, as well as documentation and field observation. Data analysis techniques in this study were carried out by collecting, reducing, presenting, and drawing conclusions. The results of this study indicate that each family applies a different parenting style. Parents with authoritarian parenting styles can help children memorize 1 juz of the Qur’an within 20 to 30 days. By using the right parenting style, there is an increase in the children’s memorization rate. Families who initially apply a permissive parenting style can guide their children to memorize one juz of the Qur’an for 2 to 3 months. And after the implementation of an authoritarian parenting style, children can finish memorizing 1 juz of the Qur’an within 20 to 30 days.